LOOKING AT THE LINKAGE BETWEEN LEARNING INDEPENDENCE, LEARNING CREATIVITY, AND ENGLISH ACHIEVEMENT OFTHE EIGHTH GRADE STUDENTS OF SMPN 1 LUMBIS - Ridwan, Ridwan; Fitriani, Dewi (Jurnal Borneo Humaniora, 2021)
This research aimed at looking at the linkage or relationship between learning independence, learning creativity, and English achievement; and finding out a significant effect of learning independence and learning creativity towards English achievement of the eighth-grade students of SMPN 1 Lumbis. Acorrelational research was employed at the eighth-grade students of SMP Negeri 1 Lumbis. 118 out of 168 students from five classes were the sample of this research by using the random sampling technique, where the Slovin formula was used to determine the students’ representation from each class. The data were gathered by utilizing questionnaires, interview, and document. The results of the analysis showed that: first, there was a simultaneous linkage or relationship between learningindependence, learningcreativity, and Englishachievement. It was proved by the value of probability from eithermultiple correlation or Pearson product moment correlation (0.000) was smaller than the level of significance (0.05). Second, learning independence and learning creativity simultaneously had a positive effect towards English achievement, in which the value of probability was smaller than the level of significance (0.000 0.05). However, there were differences in the direction of effect among the variables, where learning independence had a positive effect towards English achievement in which the value of probability was smaller than the level of significance (0.000 0.05), while learning creativity had an inconstant effect towards English achievement in which the value of probability was greater than the level of significance (0.141 0.05). The result of the determination coefficient was 30.50%, which means that learning independence and learning creativity during the covid-19 pandemic affected students’ English learning achievement by 30.50%. Other factors which influenced 69.50% were not investigated in this present study. One of these factors was the lack of online learning facilities such as unstable internet connection and internet data package.